Forgery Detection Beef with Mice Meat (Mus musculus) in Meatballs Using Real-Time Polymerase Chain Reaction (Real-Time PCR) Primer Specific for a Target Mitochondrial DNA ND-1 Gene - Tri Joko Raharjo; Gilang Aji Pratama; Irma Nuryanti; Rarastoeti Pratiwi (Universitas Gadjah Mada, 2019)
The expensive beef have encouraged counterfeiting beef on processed food products such as meatballs. Mice meat is frequently reported used for adulteration of beef. The accurate method is needed to ensure the supervision of food safety. This study reports the use of DNA testing to detect the presence of mice meat in meatballs with real-time PCR primer specific. PCR primers designed based on the ND-1 gene of mice mitochondrial DNA with the sequence are 5’-CGGCATCCTACAACCATTTGC-3’ and 5’-CGGCTCGTAAAGCTCCGAA-3’, respectively, target 294 bp DNA fragment. The real-time PCR can specifically detect the presence of the mice meat in a meatball with no detection the presence of beef, mutton, chicken, pork, and horsemeat. The method showed good precision shown by the CV of repeatability test at 2%, much lower than the requirement of < 25%. Real-time PCR was able to deliver positive results for as low as 0.5 ng DNA template, equivalent to 0.08 copies of genome DNA of mice equal to 80–150 copies of mtDNA. By using standard phenol-chloroform DNA isolation technique, this method is able to detect contamination of mice meat in meatball up to 1%. Three commercial meatballs confirmed contaminated by mice meat using the method.